Online Test using Design Banana Pi and Local Network - Brian Rakhmat Aji (IJID (International Journal on Informatics for Development), 2018)
At this time the exam using paper rated less cumbersome and inefficient. In this case the teacher will make difficult to assess the answers and take a long time to finish the job. In developing this system, the author is still in the development stage by using Banana Pi sebgai server, and use a router to a local network, this system is expected to facilitate the teacher to correct the test results.This test system uses CodeIgniter framework as a backend and frontend using material design. The system is easy to use and portable for a local network to connect them.